Compensation of unusual working schedules - Juliane Scheffel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This paper examines pecuniary aspects of work during unusual hours based on the German Time Use Data for 2001/02. The findings show positive wage premia of 9 - 10 percent for shift workers and men who work during unusual hours. There is some evidence of negative selection which suggests that men with lower potential daytime earnings have a higher propensity to choose these jobs because of the associated wage premium. The findings further show a U-shaped impact of temporal work disamenity across the wage distribution with higher wage premia paid to the extreme 5-percentiles.
Keywords: J22; J31; J33; J81; 330; shift work; non-standard working hours; time allocation; compensating wage differentials; wage premia; quantile regression; Schichtarbeit; Lohnstruktur; Zeitverwendung; Deutschland